The identity of the treehopper genus Dysyncritus Fowler, with descriptions of new related taxa (Hemiptera: Membracidae: Heteronotinae) - Evangelista, Olivia; Flórez-V, Camilo; Sakakibara, Albino M. (Zootaxa, 2014)
Dysyncritus Fowler is revised based on the examination of primary types, and restructured to exclusively accomodate Dysyncritus intectus Fowler, 1895. Allodrilus Evangelista gen. nov. (type species: Cymbomorpha nitidipennis Funkhouser, 1922 = Allodrilus nitidipennis (Funkhouser, 1922) comb. nov.) is erected with seven newly discovered taxa: A. alboferrugineus Evangelista sp. nov. (Brazil, Colombia, Guyana), A. colombiensis Flórez-V sp. nov. (Colombia), A. deitzi Evangelista sp. nov. (Ecuador), A. granulatus Evangelista sp. nov. (Ecuador), A. horizontalis Evangelista sp. nov. (Bolivia), A. intermedius Evangelista sp. nov. (Ecuador), and A. similis Evangelista sp. nov. (Peru). A key to males is provided, in addition to annotated descriptions and illustrations. Nomenclatural changes are proposed to species formerly included in Dysyncritus: Smiliorachis nubilis (Goding, 1930) comb. nov., Smiliorachis discrepans (Goding, 1930) comb. nov., and Dysyncritus lineatus Goding, 1930 (= Smiliorachis octilinea Stål, 1869 syn. nov.).